Optimal mobile device selection for round-robin data exchange via adaptive multi-criteria decision analysis. (August 2016) - Chen, Young-Long; Ke, Chih-Kun
Highlights: We provide a mobile device selection approach for round-robin data exchange. When a data exchange round is finished, an adaptive function is carried out to adjust the criteria evaluation in order to obtain a more adaptive ranking order of candidate mobile devices for the next round. As a built-in system mechanism, it requires no user intervention. Abstract: In recent years, exchanging data has become far easier with the rapidly growing popularity and increased mobility of mobile devices. However, data exchange between mobile devices is performed as a peer-to-peer communication. Each mobile device that serves as a candidate has a whole range of hardware statuses which may influence data exchange performance. Thus, the selection of a mobile device with sufficient computing resources to facilitate round-robin data exchange is an interesting process worth exploring. This study proposes an optimal mobile device selection approach for round-robin data exchange via the monitoring of the hardware status of each candidate device's system profile. A case study demonstrates the proposed approach, step by step. The experimental results show that the proposed approach can be used to improve round-robin data exchange performance. The contribution of this study is to provide an approach which selects an optimal candidate mobile device for round-robin data exchange in a local wireless communication network. Graphical abstract: